2015
DOI: 10.5812/ircmj.29933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient-Focused Clinical Pathway on Anxiety, Depression and Satisfaction of Patients With Coronary Artery Disease: A Quasi-Experimental Study

Abstract: Background:Coronary artery diseases (CAD) are associated with psychological problems such as anxiety and depression in patients. Thus, management of these problems can consider as an important intervention by health care workers, especially nurses.Objectives:The purpose of this study was to investigate the effectiveness of patient-focused clinical pathway on anxiety, depression and satisfaction of patients with CAD.Patients and Methods:In this quasi-experimental study, 138 patients suffering from CAD in a coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…According to previous studies, psychosocial stress has been found to contribute more than other traditional risk factors, and it is vastly underdiagnosed and undertreated, even more so after procedures, suggesting that more attention should be given to depression and anxiety after myocardial infarction (Barth, Schumacher, & Herrmann-Lingen, 2004). On account of high risk of stroke, severe complications, or even sudden death, most CAD patients experience helplessness, hopelessness, or worthlessness, resulting in self-reproaches and grave fear, thereby directly increasing occurrences of anxiety and depression (Benjamin et al, 2018; Fakhr-Movahedi et al, 2015; Mozaffarian et al, 2016; Pelletier et al, 2015). Care intervention programs with one or two intervention measures have been broadly utilized in cardiovascular patients for the purposes of psychological management and prognosis improvement (Fakhr-Movahedi et al, 2015; Pedersen et al, 2015; Shen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…According to previous studies, psychosocial stress has been found to contribute more than other traditional risk factors, and it is vastly underdiagnosed and undertreated, even more so after procedures, suggesting that more attention should be given to depression and anxiety after myocardial infarction (Barth, Schumacher, & Herrmann-Lingen, 2004). On account of high risk of stroke, severe complications, or even sudden death, most CAD patients experience helplessness, hopelessness, or worthlessness, resulting in self-reproaches and grave fear, thereby directly increasing occurrences of anxiety and depression (Benjamin et al, 2018; Fakhr-Movahedi et al, 2015; Mozaffarian et al, 2016; Pelletier et al, 2015). Care intervention programs with one or two intervention measures have been broadly utilized in cardiovascular patients for the purposes of psychological management and prognosis improvement (Fakhr-Movahedi et al, 2015; Pedersen et al, 2015; Shen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…On account of high risk of stroke, severe complications, or even sudden death, most CAD patients experience helplessness, hopelessness, or worthlessness, resulting in self-reproaches and grave fear, thereby directly increasing occurrences of anxiety and depression (Benjamin et al, 2018; Fakhr-Movahedi et al, 2015; Mozaffarian et al, 2016; Pelletier et al, 2015). Care intervention programs with one or two intervention measures have been broadly utilized in cardiovascular patients for the purposes of psychological management and prognosis improvement (Fakhr-Movahedi et al, 2015; Pedersen et al, 2015; Shen et al, 2018). For instance, a previous study reveals that patients’ education for 5 days contributes to anxiety and depression level reductions in CAD patients by increasing the patients’ awareness of disease risk factors, disease progression, or therapeutic interventions (Fakhr-Movahedi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations